The editor : a novel - Rowley, Steven, 1971- (G.P. Putnam's Sons, 2019)
"From the bestselling author of Lily and the Octopus comes a funny, poignant, and highly original novel about an author whose relationship with his very famous book editor will change him forever--both as a writer and a son. After years of struggling as a writer in 1990s New York City, James Smale finally gets his big break when his novel sells to an editor at a major publishing house: none other than Jacqueline Kennedy Onassis. Jackie, or Mrs. Onassis as she's known in the office, has fallen in love with James's candidly autobiographical novel, one that exposes his own dysfunctional family. But when the book's forthcoming publication threatens to unravel already fragile relationships, both within his family and with his partner, James finds that he can't bring himself to finish the manuscript. Jackie and James develop an unexpected friendship, and she pushes him to write an authentic ending, encouraging him to head home to confront the truth about his relationship with his mother. But when a long-held family secret is revealed, he realizes his editor may have had a larger plan that goes beyond the page... With lovable characters and the same intimate prose that readers loved in Steven Rowley's debut novel, Lily and the Octopus, The Editor is a poignant, insightful novel of young men and their mothers, authors and their editors, and the minefields of speaking the truth about those we love"--